2010
DOI: 10.1017/s0305000909990328
|View full text |Cite
|
Sign up to set email alerts
|

Maternal label and gesture use affects acquisition of specific object names

Abstract: Ten mothers were observed prospectively, interacting with their infants aged 0 ; 10 in two contexts (picture description and noun description). Maternal communicative behaviours were coded for volubility, gestural production and labelling style. Verbal labelling events were categorized into three exclusive categories: label only; label plus deictic gesture; label plus iconic gesture. We evaluated the predictive relations between maternal communicative style and children's subsequent acquisition of ten target n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Specifically, we examined whether children were more likely to respond with speech following different maternal gesture types. Past research has suggested that maternal gesture use helps to promote language outcomes (Goodwyn et al, 2000; Namy et al, 2000; Zammit & Schafer, 2011), and that children are more likely to respond with gestures and speech when mothers use gestures during communicative interactions (Iverson et al, 1999). Using gestures appears to help scaffold communicative interactions by providing children with more information about the spoken message, which in turn promotes comprehension (Capone & McGregor, 2004; Iverson et al, 1999; McNeil et al, 2000; Ninio & Bruner, 1978; Vygotsky, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we examined whether children were more likely to respond with speech following different maternal gesture types. Past research has suggested that maternal gesture use helps to promote language outcomes (Goodwyn et al, 2000; Namy et al, 2000; Zammit & Schafer, 2011), and that children are more likely to respond with gestures and speech when mothers use gestures during communicative interactions (Iverson et al, 1999). Using gestures appears to help scaffold communicative interactions by providing children with more information about the spoken message, which in turn promotes comprehension (Capone & McGregor, 2004; Iverson et al, 1999; McNeil et al, 2000; Ninio & Bruner, 1978; Vygotsky, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Deictic gestures include pointing, showing, giving, and other gestures that are used to indicate the object or event that is the focus of the communicative interaction, such as tapping or touching an object (Bates, 1976; Iverson et al, 1999; Masur, 1990; O’Neill et al, 2005; Tfouni & Klatzky, 1983; Zammit & Schafer, 2011). The most common and important deictic gestures for communication are pointing gestures (Iverson & Goldin-Meadow, 2005; Ozçalişkan & Goldin-Meadow, 2005; Tomasello, Carpenter, & Liszkowski, 2007; Tomasello, 1988) because a pointing gesture can help to direct child attention to the object or event that is the focus of the communicative interaction (Bates et al, 1975), thus, helping to maintain infant and child attention (Bangerter, 2004; Liszkowski, Carpenter, Henning, Striano, & Tomasello, 2004; Louwerse & Bangerter, 2010; Tomasello et al, 2007).…”
Section: Importance Of Parental Gesture Use In Language Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that no articles describing the influence of the family environment and the importance of social relationships on the lexical acquisition and development were found, as well as the impacts on the child population, however, there are studies showing the importance of the parental communicative style and profile for the overall language development 25,26 .…”
Section: Brancalioni Et Al 2011mentioning
confidence: 99%